Sobre a piedade (eleos) e a indignação (nemesan) na Retórica de Aristóteles - Daniel Felipe Couto Vieira Silva (2020)
The purpose of our dissertation is to investigate what we called “the question of passions” and to point out how pity (eleos) and indignation (nemesan) are inserted in the context of Aristotle's rhetorical art (techne rhetorike). To this end, we present an interpretative perspective on the passions in Aristotle's work, punctually identifying how the pathe are shown in the Corpus Aristotelicum (mainly in Physics, Metaphysics, On the Soul, Nicomachean Ethics and Politics) and later articulating them with the Rhetoric and the Poetics. In the first part of our work, we indicate how passions are understood in the philosophy of the Stagirite, and then we expounded the Book II of Rhetoric. In this analysis, after elucidating the general concepts of the pathe, we focus on the description of the necessary conditions for the conduction of the passions by the discourse. Articulating the three fundamental elements of rhetorical art, ethos, pathos and logos, we present the conception of passions as a primordial characteristic of persuasion. Finally, by comparing aspects of Rhetoric and Poetics, we examine how pity (eleos) and indignation (nemesan) can be articulated in it. For such, we take into consideration the importance of these two passions, their effects on the polis and their ethical-aesthetic elements, aiming to contribute to contemporary discussions about the role of passions in Aristotelian philosophy.